The effects of private speech on the speaking proficiency of young Jordanian English as a Foreign Language students - Rababah, Luqman; Almwajeh , Motasim; Al-Khawaldeh , Nisreen Naji; Al-Shboul , Othman Khalid; Issa Falah Bani Amer, Mamoun; Dakamsih, Nusaibah J. (East European Journal of Psycholinguistics, 2023)
This research examined how private speech affects the speaking ability competency in young Jordanian English as a Foreign Language students. The mixed-methods research gathered quantitative and qualitative data from 50 Jordanian EFL students aged 10-12. Pre- and post-tests of speaking skill mastery provided quantitative data, and observations and semi-structured interviews were also conducted to provide qualitative data. Private speech exercises significantly improved participants’ speaking skills. Private speech improved participants’ fluency, accuracy, and complexity. The qualitative data also showed that private speech helped individuals speak English with confidence and less nervousness. The research reveals that private speech exercises might help young Jordanian EFL students improve their speaking skills. EFL instructors and curriculum designers in Jordan may want to include private speech exercises to improve students’ speaking and language abilities. Private speech activities should be studied in additional circumstances and age ranges. Disclosure Statement No potential conflict of interest was reported by the authors. * Corresponding author: Luqman Rababah, 0000-0002-3871-3853 luqman@jadara.edu.jo